Outbreak-Associated Vibrio Cholerae Genotypes with Identical Pulsotypes, Malaysia, 2009 - Teh, C.S.J.; Suhaili, Z.; Lim, K.T.; Khamaruddin, M.A.; Yahya, F.; Sajili, M.H.; Yeo, C.C.; Thong, Kwai Lin (2012)
A cholera outbreak in Terengganu, Malaysia, in November 2009 was caused by 2 El Tor Vibrio cholerae variants resistant to typical antimicrobial drugs. Evidence of replacement of treatable V. cholerae infection in the region with antimicrobial-resistant strains calls for increased surveillance and prevention measures.